2018
DOI: 10.1038/s41467-018-06717-w
|View full text |Cite
|
Sign up to set email alerts
|

Physical reality of the Preisach model for organic ferroelectrics

Abstract: The Preisach model has been a cornerstone in the fields of ferromagnetism and ferroelectricity since its inception. It describes a real, non-ideal, ferroic material as the sum of a distribution of ideal ‘hysterons’. However, the physical reality of the model in ferroelectrics has been hard to establish. Here, we experimentally determine the Preisach (hysteron) distribution for two ferroelectric systems and show how its broadening directly relates to the materials’ morphology. We connect the Preisach distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 57 publications
(96 reference statements)
1
29
0
Order By: Relevance
“…a projection of the Preisach distribution, 47 is of Gaussian form, which matches experimentally obtained results on linear BTAs from our previous work. 35 Being centered around the same B0.35 V nm À1 value, this distribution is narrower for BTA-C6/2 compared to C8, which indicates lower disorder in the box of the former compound. This may be the underlying reason for the faster switching and higher activation field in C6/2, as seen from comparison of averaged switching characteristics over 9-stacks in Fig.…”
Section: Box Switchingmentioning
confidence: 90%
See 1 more Smart Citation
“…a projection of the Preisach distribution, 47 is of Gaussian form, which matches experimentally obtained results on linear BTAs from our previous work. 35 Being centered around the same B0.35 V nm À1 value, this distribution is narrower for BTA-C6/2 compared to C8, which indicates lower disorder in the box of the former compound. This may be the underlying reason for the faster switching and higher activation field in C6/2, as seen from comparison of averaged switching characteristics over 9-stacks in Fig.…”
Section: Box Switchingmentioning
confidence: 90%
“…We have previously shown that polarization switching in BTAs is dispersive and proceeds through extensive nucleation, which restricts further monotonous growth of ferroelectric domains. 23,35 This kind of switching process is typical for polycrystalline, disordered ferroelectrics and can be described by so-called nucleation-limited switching (NLS) models. 36,37 With thermal activation included, the NLS model can successfully describe the temperature dependence of ferroelectric parameters.…”
Section: Coercive Fieldmentioning
confidence: 99%
“…40 In a recent work we presented an experimental approach to measure this Preisach distribution (PD) and established a direct connection between the material's morphology and the width and shape of the PD. 41 However, to evaluate the width of the distribution, a projection of the PD is sufficient, which is straightforwardly obtained as the switching current response to a triangular voltage signal, i.e. the derivative of the macroscopic polarization hysteresis loop.…”
Section: Vs Remnant Polarization and Disordermentioning
confidence: 99%
“…The extracted standard deviation s was used as a proxy for structural disorder and the amount of amorphous material present in the active layer. 41 The obtained s parameter varied in range 0.1-0.45 for BTA-C6. The measurements were performed at 60 1C to compare the behaviour among the BTA homologues (see below), at which they all are in the columnar-hexagonal liquid-crystalline state and ferroelectrically switchable (see ESI †).…”
Section: Vs Remnant Polarization and Disordermentioning
confidence: 99%
“…The Preisach model [1] has been a mainstay to study hysterical behaviors in a wide range of actuators systems [2]- [6] and ferroelectric-, bio-material dynamics [7]- [10], by both automation engineering and material science communities. In particular, Preisach density (PD) has drawn increasing attention for interpreting material properties from hysteresis measurements [11]- [14]. For example, recent work [11] provides strong physical basis for the mathematical Preisach model to explain polarization switching dynamics, rendering it a powerful tool for providing guidelines of ferroelectric storage applications.…”
Section: Introductionmentioning
confidence: 99%